2020
DOI: 10.3390/plants9060742
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effects of Bidens pilosa L. var. radiata Sch. Bip. on the Tuber Sprouting and Seedling Growth of Cyperus rotundus L.

Abstract: Bidens pilosa L. var. radiata Sch. Bip. (BPr) had been found capable of excluding Cyperus rotundus L. (CR) from its vegetation in fallow fields. Both allelopathy and competition of BPr were able to limit the growth of CR, but this has not been extensively investigated. To verify the two effects of BPr on CR management, density-dependent experiments and interspecies competitions with the application of activated carbon were conducted. The effects of BPr soil and its residues on the reproduction of CR were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
9
1
Order By: Relevance
“…Previous studies demonstrated that residues of Cobbler's pegs could significantly reduce the sprout reproduction of Cyperus rotundus L. in the upland field [18] and inhibited the growth of weeds in the paddy field [12,53]; however, in the present study, this plant exerted strong phytotoxicity on its seed germination in the controlled (Figure 2) and seminatural conditions (Figure 6), but less phytotoxicity in the natural conditions (Figures 8 and 9). The phytotoxicity of donor plants to the target plants depended on the concentration, movement and persistence of phytotoxins in the field condition [54].…”
Section: Responses Of Germinationcontrasting
confidence: 65%
See 2 more Smart Citations
“…Previous studies demonstrated that residues of Cobbler's pegs could significantly reduce the sprout reproduction of Cyperus rotundus L. in the upland field [18] and inhibited the growth of weeds in the paddy field [12,53]; however, in the present study, this plant exerted strong phytotoxicity on its seed germination in the controlled (Figure 2) and seminatural conditions (Figure 6), but less phytotoxicity in the natural conditions (Figures 8 and 9). The phytotoxicity of donor plants to the target plants depended on the concentration, movement and persistence of phytotoxins in the field condition [54].…”
Section: Responses Of Germinationcontrasting
confidence: 65%
“…Many Asteraceae species, such as Ageratum conyzoides L. [46], Helianthus annuus L. [47], Parthenium hysterophorus L. [48] and Wedelia trilobata L. [49], possess autotoxicity to regulate their vegetation regeneration and expansion. Several studies indicated that the plant extracts of Cobbler's pegs [7,18,[50][51][52] contained phytotoxins (i.e., phenolics and PHT) that inhibited seed germination and seedling growth of many other species. In the present study, we investigated the autotoxicity of Cobbler's pegs residue from the laboratory to the field and found that the residue or its extract of this plant was able to exert phytotoxicity on its seed germination and radicle growth in the laboratory, pot and field experiments.…”
Section: Autotoxic/phytotoxic Effects Of Residues On the Seed Germination And Radicle Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Eugenol was phytotoxic against a range of weeds such as Taraxacum officinale (L.) Weber ex F.H.Wigg. [ 58 ], Amaranthus retroflexus L. [ 59 ], Chenopodium album L. [ 60 ], Echinochloa crus-galli (L.) P.Beauv., Phalaris minor Retz., Ageratum conyzoides (L.) L., Leptochloa chinensis (L.) Nees, Bidens Pilosa L., and Commelina benghalensis L. [ 58 ], being promising as a bio-herbicide.…”
Section: Resultsmentioning
confidence: 99%
“…At present, there are no highly selective and safe bio-herbicides for controlling barnyard grass in rice fields. Evaluation of allelochemicals, especially their inhibition functions, is an effective method for identifying potential herbicides [ 3 ]. Plant essential oils can function as allelochemicals and therefore serve as a resource pool which can provide effective allelochemicals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%